Prevalence of Dermatophytic Infections among Students of Nigerian Higher Institution Using Occlusive Leather Footwear - , M. Umar; , M. B. Mustapha; , I. B. Mohammed; , A. A. Aliko; , I. Y. Tafinta; , B. Adenuga (Archives of Current Research International, 2016)
Aim: Prevalence of dermatophytic infections amongst students of Nigerian higher institutions using occlusive leather footwear was carried out. The aim was to evaluate the prevalence of dermatophytic infection associated with occlusive leather footwear worn by students of Nigerian Institute of Leather and Science Technology (NILEST), Zaria, with view to isolate, enumerate, compare the fungal loads between students who use occlusive footwear alongside with socks and those who do not, and microscopically identify the etiological agents associated with leather footwear. Place and Duration of Study: The study was conducted at the Department of Science Laboratory Technology, Nigerian Institute of Leather and Science Technology, Zaria, Kaduna state, Nigeria for the period of February, 2014 to July, 2014. Methodology: Forty swab samples were collected from the feet surface of students that wear occlusive leather footwear at Nigerian Institute of Leather and Science Technology (NILEST), Zaria, Kaduna State, Nigeria; twenty swab samples from those who use occlusive footwear with socks and also twenty swab samples from those that do not use occlusive footwear with socks. The swab samples were inoculated on solidified Sabouraud’s Dextrose Agar (SDA) and incubated for 4 weeks and examined at 2 to 3 days intervals for fungal growth at temperatures of 28°C and 37°C. After incubation, the colonies developed on th e medium plates were counted by hemacytometry and recorded. Potassium hydroxide microscopic observation was used to identify the isolated moulds. Results: The total prevalence of dermatophytic infections in the study area was found to be 85%, and the samples collected from the students using occlusive footwear without socks were found to harbor more fungal loads (72.5%) compared to those collected from students that use occlusive leather footwear with socks (27.5%). Thus, using socks reduces the level of dermatophytic fungal load for occlusive footwear. The dermatophytes isolated include Epidermophyton, Trichophyton and Microsporum species as well as yeast species. Conclusion: Both students that wear occlusive leather footwear with socks and without socks harboured dermatophytic fungi, and the overall prevalence of dermatophytic infections in the study area was determined as 34 (85%). But, the infection is more rampant in the students that wear occlusive leather footwear without socks to dry the excessive sweat in their feet resulting from overstay in footwear or rigorous athletic activities.